Anticoagulation for the prevention of stroke in non-valvular AF in general practice: room for improvement - Adam Ioannou; Sofia Metaxa; George Kassianos; Constantinos G Missouris (BioExcel Publishing Ltd, 2016)
Objective: Our aim was to assess whether the recommendations and guidelines for thromboprophylaxis in patients with atrial fibrillation (AF) have been adopted in general practice (GP). Methods: We conducted a retrospective study using the GP computer database (Hatfield, UK) on all 9400 patients to assess the quality of anticoagulation in patients with a recorded diagnosis of AF. Results: Of the 180 patients with a diagnosis of AF, 107 (59.4%) were treated with warfarin, 19 (10.6%) with a novel oral anticoagulant (NOAC), 31 (17.2%) with aspirin or clopidogrel, and 23 (12.8%) received none. Thirty-seven patients (34.6%) who were taking warfarin had a time in the therapeutic range (TTR) of less than 65%. Forty-five (27.6%) of the 163 patients who had a CHA2DS2VASc score of two or more were not prescribed a vitamin K antagonist (VKA) or a NOAC. None had a HAS-BLED greater than the CHA2DS2VASc score. Conclusion: Our study demonstrates that one in four patients with non-valvular AF, at risk of a stroke, is not being adequately treated with an oral anticoagulant in primary care. The majority were treated with warfarin, a third of which had a low TTR. A high proportion of patients are prescribed antiplatelet therapy instead. This is despite overwhelming evidence that VKAs and NOACs, and not aspirin or clopidogrel, improve outcome in patients with non-valvular AF. We suggest that a review of GP practice databases should be considered to identify patients with non-valvular AF, at risk of a disabling or fatal event, and measures taken to initiate anticoagulant therapy.